Acute Pancreatitis Following Orlistat Therapy: Report of Two Cases - Ahmad, Faheem Asem; Mahmud, Sajid (JOP. Journal of the Pancreas, 2016)
Context Orlistat is a pancreatic lipase inhibitor licensed for the treatment of obesity. As obesity rates increase and non-prescription dispensing of orlistat increases, an awareness of its adverse effects is of crucial importance as complications arise more frequently from increased use. Orlistat induced pancreatitis has been described only once previously, but without a diagnostic increase in serum amylase. Case report We report the case of two patients who developed severe acute abdominal pain and elevated pancreatic enzymes at 2 and 10 days after starting orlistat. In one case no alterative precipitant was identified. In the other, a predisposing history of pancreatic injury was present. In both cases all other contributory causes were excluded. Conclusions Our reports suggest orlistat can trigger drug induced acute pancreatitis in certain patients. For patients presenting with abdominal pain soon after commencing orlistat, a diagnosis of pancreatitis must be considered. We also recommend cautious use of orlistat in patients at risk of pancreatic injury. Image: Orlistat (Author: Boghog; Wikimedia Commons).